Soft-scape construction specification in Malaysia: comparison between government and private sectors - Ab Sani, Jasasikin; Othman, Noriah (2011)
Since the construction activities involve the process and products, the definition of quality standard in construction might not be much different to definition on quality standard for other processes and products. Therefore, the quality standard in landscape construction is a continuous process of fulfilling the specific requirement that is adequate and agreeable to all stakeholders. It can be summarized that the quality standard in relation to the landscape construction industry can be defined as a document, containing sufficient technical specifications to be used consistently as rules and guidelines to ensure that materials and works conform to the project requirements. This paper reviews the status of standards specification in Malaysia. Standard Specification documents from related government agencies and selected private company in Malaysia had been collected for comparison. Comparison has been made on every item in quality standard from three parties involved to identify the similarities and differences.